Online Learning System for Kampus Merdeka : Innovative Learning In Covid-19 Pandemic - Budi Harijanto; Meyti Eka Apriyani; Elok Nur Hamdana (IJORER : International Journal of Recent Educational Research, 2021)
Innovations in learning media for "Kampus Merdeka" currently require students active roles in online lectures and interact with lecturers and college friends to be able to use social networking media. Massive Online Open Course (MOOC) is web-based learning that can be accessed anywhere and anytime by integrating technology into the learning process that can help improve understanding of the material. In this reasearch an online learning design using MOOC as a solution in the implementation of "Kampus Merdeka" using Web Programming Design course. The reason for choosing these subjects is because practical learning activities require an understanding of a strong theoretical basis. Learning Outcomes in this course are students can understand the basics and concepts in website before finally carrying out the practicum. In the study sample population in the MOOC Web Programming course which was attended by 30 students from various backgrounds, it was seen that on average 78.2% interesting join the MOOC online class. The results of this percentage show that students are interested in joining MOOC online classes because they can provide a self-development model, namely institutional (materials that are in accordance with the syllabus), pedagogical in the form of learning videos) and technical (in the form of practicums)